Irradiation Preservation of Meat and Meat Products and its Effect –A Review - Jayathilakan, K.; Sultana , Khudsia (Journal of Meat Science, 2018)
Radiation processing is one of the emerging technologies to ensure the safety of meat and meat products. Microbial contamination of meat is a  serious concern for both meat products and consumers. Irradiation has emerged as an alternate technology to eliminate microbial contamination  and several countries have approved it. Wide acceptability of radiation processed meat products will depend upon quality parameters such as  oxidative changes and organoleptic attributes. Food irradiation can cause changes in both macro and micro nutrients, but these changes are  small. Irradiation is not alone in its ability to produce nutritional changes. Many food processes, notably cooking and heating in general, also  cause nutrient loss, often to a greater run. No significant effects on essential amino acids have been observed in beef, fish or many other food  stuffs even at sterilizing doses. Irradiation affects flavour and texture of dairy products and eggs. On the whole irradiation of food does not  cause nutrient losses to the extent that there could be an adverse effect on the nutritional status of the individuals consuming these foods.  Development of shelf stable meat and meat products is a challenging task due to physico-chemical, microbiological and sensory alterations  during storage. Lot of thrust is being given in the application of radiation processing in meat sector due to its microbial safety. Maintaining  and delivering quality and safety products both in civilian and service sectors is the need of the hour. Even though irradiation can ensure  complete microbial sterility it can lead to lipid and protein oxidation due to the formation of free radicals which can cause flavour changes. The  adverse implications due to lipid and protein oxidation being observed in meat, poultry products can be suppressed by selecting proper natural  antioxidant combinations. Irradiation can be employed as a critical control point in the meat, poultry chain and such an intervention is essential  in ensuring the safety of products.
Keywords: Meat; Irradiation; Protein; Lipid Oxidation; Preservation